Non-invasive Molecular Detection of Minimal Residual Disease in Papillary Thyroid Cancer Patients - Almubarak, Hannah; Qassem, Ebtesam; Alghofaili, Lamyaa; Alzahrani, Ali S.; Karakas, Bedri (Frontiers in Oncology, 2020)
Background: Papillary thyroid cancer (PTC) is the most common type of thyroid malignancy. Serum thyroglobulin (Tg) levels are used to monitor PTC treatment response and recurrences however, in about 25% of the cases the sensitivity of this method is compromised due to either the presence of neutralizing anti-Tg antibodies (TgAb) or the absence of Tg in less differentiated tumors. Up to 80% of PTC tumors harbor the c.1799T>A hotspot mutation in the BRAF gene (BRAFV600E). Here, we assessed the potential use of plasma cell-free BRAFV600E mutant tumor DNA (ctDNA) levels in determining the minimal residual tumor status of PTC patients. Methods: Patients were classified as either having persistent disease (PD) or no evidence of disease (NED) based on clinicopathological assessments. Tumor BRAFV600E status was determined by both direct sequencing and digital PCR. Plasma total cell-free BRAFV600 wild type DNA (cfDNA) and ctDNA fractions circulating in the plasma of PTC patients were determined by an emulsion based-digital PCR and total ctDNA was quantified by 3D digital PCR. The total ctDNA levels (copies/ml) were then compared to patients’ clinicopathological features. Results: About 74% (28/38) of tumors harbored the BRAFV600E mutation. Percent plasma ctDNA fractions for PD patients with BRAFV600E tumors ranged from 0 to 2.07 %, whereas absolute plasma ctDNA copies ranged from 0 to 62 copies. The ctDNA levels accurately detected tumor burden of PTC patients whose tumors harbored BRAFV600E; median plasma ctDNA copy numbers were significantly higher (Wilcoxon test, p=0.03) in patients with metastasis (MET) (20 copies/ml) compared to patients with non-metastatic (non-MET) tumors (1 copy/ml). The plasma ctDNA levels (copies/ml) accurately determined the disease status of PTC patients with sensitivity of 86% and specificity of 90% as compared to 78% sensitivity and 65% specificity determined by serum Tg levels (ng/ml) with areas under the curves (AUC) of 0.88 and 0.71, respectively. Intriguingly, plasma total cfDNA levels were significantly higher in patients with no evidence of residual disease (NED) compared to persistent disease (PD) patients. Conclusions: Our study supports the clinical applicability of using plasma ctDNA as biomarker to determine the residual tumor status and tumor burden of PTC patients.